2018
DOI: 10.1155/2018/9162921
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio Are Not Clinically Useful in Predicting Prognosis in Early Stage Cervical Cancer

Abstract: Background An objective of this study was to determine the prognostic role of neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in patients with cervical cancer (CC) stages IA2-IB1. Methods The study included 484 patients who underwent radical hysterectomy with pelvic node dissection. The associations of preoperative NLR and PLR with clinicopathologic characteristics and oncological outcomes were analyzed. The cut-off values of NLR (=1.8) and PLR (=119) were set as medians. Results The clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…There is a possible impact of genetic factors to the risk of HPV infection progression to cervical precancer and CC [5]. It has been suggested that the standard primary treatment of CC includes radiotherapy (RT), or radical hysterectomy with pelvic lymph node dissection (RHND), or a combination of RT and platinum-based chemotherapy [6]. Cisplatin (DDP) is a widely-used potent chemotherapeutic drug for the treatment of CC, while its effectiveness is restricted by the resistance development [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a possible impact of genetic factors to the risk of HPV infection progression to cervical precancer and CC [5]. It has been suggested that the standard primary treatment of CC includes radiotherapy (RT), or radical hysterectomy with pelvic lymph node dissection (RHND), or a combination of RT and platinum-based chemotherapy [6]. Cisplatin (DDP) is a widely-used potent chemotherapeutic drug for the treatment of CC, while its effectiveness is restricted by the resistance development [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the standard primary treatment of CC includes radiotherapy (RT), or radical hysterectomy with pelvic lymph node dissection (RHND), or a combination of RT and platinum-based chemotherapy [6]. Cisplatin (DDP) is a widely-used potent chemotherapeutic drug for the treatment of CC, while its effectiveness is restricted by the resistance development [6]. Consequently, the recognition of novel prognostic markers might be helpful for offering more personalized medical treatment for CC.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the pretreatment NLR was significantly associated with tumor grade, advanced FIGO stage, LVSI, LN metastasis and recurrence, which would influence the alternative of therapy strategies. These results are consistent with studies showing that neutrophilia and leukocytosis are associated to worse outcomes in patients with locally advanced and recurrent cervical cancer 29 31 , 46 48 .…”
Section: Discussionsupporting
confidence: 92%
“…Fourteen studies comprising 6041 patients with cervical cancer were included 20 , 29 – 41 . Characteristics of included studies are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation